The Nature of the Right to Personal Data: A Civil Law Perspective - L. V. Shvets (Сибирское юридическое обозрение, 2024)
In today’s context of growing volumes of personal data and the increasing number of legally significant actions that can be conducted with access to such data, the importance of legal protection for personal data has become more pronounced. This paper aims to examine the nature of the right to personal data. Based on an analysis of Russian legislation, the Author concludes that there exists an unnamed, independent subjective right, which serves to enable the data subject to control and define the conditions for data processing, as well as to protect personal data from unauthorized use. The study critically evaluates the current scientific debate regarding the nature of this right. Three primary approaches in the academic discourse on the autonomy of this right are identified, tentatively categorized as the “ignoring”, “denying”, and “recognizing” approaches. The Author notes the lack of a uniform scientific approach to naming this right and suggests designating it as “the right to the inviolability of personal data”. This right is characterized as an independent, subjective, personal non-property, and absolute civil right. The paper further explores the conditions under which this right arises and terminates. Specifically, it originates at the birth of an individual and terminates when the purpose of personal data processing ceases, typically upon the death of the individual whose data was processed. The need for legal succession is justified to allow heirs to ensure the inviolability of the testator’s personal data if its processing continues posthumously. In distinguishing between the right to the inviolability of personal data and the right to privacy, the Author argues that these are distinct subjective rights. They are interconnected only in theoretical frameworks that enable the use of protective measures for one right when the other is infringed. A trend in judicial practice has been identified, where courts recognize the existence of a right to personal data. Although not explicitly named, this right is nonetheless afforded legal protection.